Pelatihan Keterampilan Bahasa Inggris Komunikatif bagi Pedagang Souvenir di Sentra Kerajinan Gerabah Sasak - Terasne Terasne; Dira Permana; Ahmad Hanan; Sudirman Sudirman; Baiq Sumarni (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service program aims to improve English communication skills for pottery souvenir traders who sell around the Sasak Pottery craft center, Penujak Village, Central Lombok Regency. The implementation of this service uses a transfer of knowledge-based training method consisting of preparation, implementation, and evaluation activity. The service activity partners are souvenir traders at the Sasak Pottery Craft Center, totaling 30 people. The evaluation instrument for this activity uses an English conversation test and is analyzed descriptively. The results of the implementation of the activities show that: 1) The training participants, consisting of souvenir traders at the Sasak Pottery craft center, have gained knowledge both theoretically and practically regarding good communication skills in English. 2) Souvenir traders have been able to use English as a means of communication to promote and offer various types of handicraft products to foreign guests. It is hoped that this training activity can positively contribute to improve the residents' welfare, especially for makers and/or sellers of pottery souvenirs around Penujak village.